3D geometallurgical characterization of coal mine waste rock piles for their reprocessing purpose - Ayoub El Aallaoui; Abdellatif Elghali; Rachid Hakkou; Yassine Taha; Mostafa Benzaazoua; Mustapha El Ghorfi (International Journal of Coal Science & Technology, 2025)
Abstract Jerada coal mining generates extensive coal mine waste rock (CMWR) piles rich in valuable minerals, posing environmental challenges and economic opportunities. This study examines reprocessing feasibility through 3D geometallurgical characterization. Sampling used down the hole hammer drilling technique (DTH) and drone surveys for topographical precision. Over 620 samples from (T01, T02, T08) underwent comprehensive analyses including particle size distribution, x-ray fluorescence (XRF), total sulfur/carbon analysis (S/C), and inductively coupled plasma mass spectrometry (ICP-MS) for physical–chemical characterization. Mineralogical aspects were explored via optical microscopy (OM), X-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microanalysis (EPMA), and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Quantitative mineral evaluation by scanning electron microscope (QEMSCAN) provided mineral insights. Chemical data was used in a 3D block model to quantify residual coal. Results for the three examined CMWR piles (T01, T02, and T08) showed varying D80 from 160 to 300 µm, notable carbon content averaged 12.5 wt% (T01), 16 wt% (T02), and 8.5 wt% (T08). Sulfur presence exceeded 1 wt% in T08, and potential environmental concerns due to iron sulfides. Anthracite liberation was below 30 wt%. 3D modeling estimated a total volume of 7 Mm3, mainly from T08, equaling 11.2 Mt. With its high carbon content and substantial tonnages, re-exploitation or alternative applications could minimize these CMWR piles environmental impact.